Efficacy of occupational therapy with supportive techniques on Social and Occupational Functioning among persons with Schizophrenia - Upendra , Singh (International Journal of Psychosocial Rehabilitation, 2017)
Background: It is well understood that psychotherapy attempts to alleviate emotional suffering and to enhance personality adjustment through planned psychosocial interventions. But it is unfortunate that much of the emphasis has been placed on the ill effects of psychotic disorders like schizophrenia and thus researches are concerned with destructive pathological effects and ignores the fact that constructive regenerative influences may be present. No matter how much victimized an individual with schizophrenia be by his symptoms, he is always capable of some determinate learning under encouraging circumstances. Many opportunities exist in the environment of individuals suffering with schizophrenia that lead them to implement a corrective influence on their life. Unfortunately, individuals with schizophrenia do not take advantage of them because they may be unaware of their potential, or because he distorts their meaning. Thus, the study used occupational therapy and supportive techniques to help individuals with schizophrenia in recognizing their potentials and utilizing resources in the environment to help adjust in their daily life. Aim: Aim of the study was to assess efficacy of occupational therapy with supportive technique on socio-occupational functioning among persons with schizophrenia. Methodology: It was a hospital based study in which pre and post with control group design was used. To select the sample purposive sampling technique was used in this study. Results: Result showed that participants of the experimental group after receiving occupational therapy with supportive technique had significant improvement in their socio-occupational functioning.Conclusion: Occupational therapy when complemented with techniques of supportive therapy helps individuals with schizophrenia to restore to an adaptive equilibrium in their life